The Digitalized Zakat Management System in Malaysia and the Way Forward - Muhammad Ikhlas Rosele; Abdul Muneem; Noor Naemah Binti Abdul Rahman; Abdul Karim Ali (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
The development of technology and innovation has a significant influence on the current financial markets. Introducing new business models and transferring from traditional markets to the digital markets through those technologies are some ways of digital transformation. Zakat system has been a great part of Islamic economics and the financial system which has to embrace digitalization to be compatible with the current digital era. This research aims to address the current status of digitalization about the zakat management system in Malaysia and to explore the necessary improvement in embracing the digitalization by the zakat institutions. The research adopts a qualitative research approach where it collects the data from various sources such as books, journals, conference papers, and other relevant websites. To analyze the data, the research employs a descriptive and exploratory research technique. This study finds that despite having websites by the zakat institutions in Malaysia, the zakat system has a lack of data set of aṣnāf and proper data for the collected and distributed funds. Digital transformation is needed to observe the check and balance of the zakat funds’ collection and distribution. In addition, human development through zakat funds needs to embrace more development through digitalization. Moreover, the zakat institutions are encouraged to advance their readiness and understanding of technologies and innovation to embrace digital assets and their zakat-ability.